PSYCHOLOGICAL DETERMINANTS OF INTERPERSONAL TRUST IN YOUNG PEOPLE - Shulga, Galyna; Vaschenko, Alina (Personality and environmental issues, 2025)
The article presents a theoretical and empirical study of the psychological determinants of interpersonal trust in adolescents. The relevance of the study is due to the complexity and ambiguity of the processes of socialization of youth in modern society, which is characterized by rapid changes, information overload, high levels of uncertainty and psychological pressure. In the face of such challenges, the study of individual strategies for coping with stress becomes particularly important, particularly during adolescence, when basic character traits are formed, the foundations of future interpersonal relationships are laid, and mechanisms of self-regulation and self-support are developed. The aim of the article is to identify the psychological determinants of interpersonal trust in adolescents. The theoretical part of the work analyzes modern approaches to defining the concept of "coping behavior", the classification of coping strategies (problem-oriented, emotional-oriented, maladaptive, etc.), and also reveals the essence of interpersonal trust as a psychological construct that affects the nature of social interaction, emotional comfort, and personal stability. Empirical research has shown that individuals with a high level of interpersonal trust are more likely to use adaptive coping strategies: constructive thinking, seeking support, planning actions, and positive reappraisal of situations. In contrast, young men with low levels of interpersonal trust are prone to problem avoidance, emotional isolation, self-blame, and passive acceptance. The results suggest that interpersonal trust is an important predictor of effective adaptation to stressful influences and plays a key role in the formation of constructive coping behavior. The presence of stable, emotionally supportive interpersonal relationships increases the internal resources of the individual, contributes to the development of self-confidence and the formation of a positive self-concept. At the same time, a lack of trust, emotional closure, and a tendency toward social isolation significantly complicate self-regulation processes, reduce psychological resilience, and can lead to the development of anxiety or depression.. The psychological determinants of interpersonal trust in adolescents are determined by a combination of individual characteristics of the emotional-volitional sphere, the level of self-regulation, self-esteem, as well as dominant coping strategies. According to the results of the study, the development of interpersonal trust is facilitated by the presence of constructive coping strategies, such as positive reappraisal, problem-solving planning, and seeking social support. Individuals with high levels of interpersonal trust demonstrate a higher ability for emotional self-regulation, openness in communication, and greater confidence in themselves and their surroundings. At the same time, young people with low levels of trust tend to have a predominance of unique or maladaptive coping strategies, which indicates the need for psychological support and the development of emotional intelligence.